Characterization of Some Barley Cultivars (H. Vulgare spp.) for their Response to Iron Deficiency on Calcareous Soil - RUSTU KARAMAN, M.; SAHIN, SEZER; KANDEMIR, NECDET; COBAN, SERPIL; SERT, TUBA (Asian Journal of Chemistry, 2010)
The iron efficiency and responsive barley genotypes will provide valuable genetic resource for sustaining the optimal yields and quality of barley cultivars. This characterization for developed genotypes under the varied soil conditions will be useful for sustainable agriculture and environmental aspect. For this aim, a pot experiment, based on a completely randomised design with three replications, was conducted using calcareous soil. 20 Barley varieties of Tarm-93, Kearney, Orza, Kaya, Morex, Herrington, Ince-2004, Rihane, Baronesse, Golden Promise, Avustralya, Steptoe, Yesevi-93, Schuyler, NE-93760, Bulbul, Barke, Dicktoo, Ozdemir-2005 and Yerçil-147 were used for this study. Ferrous sulphate monohydrate as iron fertilizer at the levels of 0 and 10 mg Fe kg-1 were applied to the pots. After harvest, dry matter yield, tillering number and length of the plants were recorded. Total P, Fe, Cu, Zn and Mn concentrations in tops of barlyes were also determined. Dry weight (DM) and total iron content of the plants were used to calculate the efficiency index parameter for classification of genotypes. The parameter of iron efficiency index (EI) was changed depending on the plant genotypes and iron levels. This classification method also served for the characterization of genotypes as ER (efficient-responsive), ENR (efficient non-responsive), IR (inefficient responsive) and INR (inefficient non- responsive). As a result of this classification, the barley genotypes of Avustralya, Yesevi-93, Steptoe, Ince-2004, Baronesse, Herrington, Yerçil-147 were characterized as ER, whereas Bulbul and Ozdemir-2005 was characterized as ENR seems to be valuable for iron efficiency.